2015
DOI: 10.1111/ppa.12427
|View full text |Cite
|
Sign up to set email alerts
|

Testing and modelling the potential of three diploid plants in Poaceae as a new pathosystem to investigate the interactions between cereal hosts and cereal cyst nematode (Heterodera avenae)

Abstract: Cereal cyst nematode (CCN), Heterodera avenae, is one of the most important pathogens of wheat worldwide, and causes significant yield losses. Research on CCN-wheat interactions is hampered by the lack of an effective model pathosystem. This study investigated the potential of the model cereal Brachypodium distachyon (Bd21-3) and diploid wheat 2A (G1812) and 2D (AL8/78) as model hosts for CCN. Nematode infection analysis showed that although some CCN penetrated Bd21-3 roots, these nematodes failed to develop t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
3
1
Order By: Relevance
“…In this research, we evaluated the sensitivity distachyon is a host of CCN though not very susceptible. It was reported that Bd21-3 was not a host for CCN, as nematodes penetrated roots but failed to develop to the later developmental stages or form cysts (Kong et al 2016). While in this research, Bd21-3 formed 0.2±0.4 (0-1) cysts/plant, which was not consistent with previous report.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…In this research, we evaluated the sensitivity distachyon is a host of CCN though not very susceptible. It was reported that Bd21-3 was not a host for CCN, as nematodes penetrated roots but failed to develop to the later developmental stages or form cysts (Kong et al 2016). While in this research, Bd21-3 formed 0.2±0.4 (0-1) cysts/plant, which was not consistent with previous report.…”
Section: Discussioncontrasting
confidence: 92%
“…While in this research, Bd21-3 formed 0.2±0.4 (0-1) cysts/plant, which was not consistent with previous report. These two contrary results might be due to different CCN populations inoculated, that is, we inoculated DX CCN while Kong et al (2016) used population they maintained in a greenhouse by themselves.…”
Section: Discussionmentioning
confidence: 87%
“…A breakthrough point in Brachypodium research was the genome sequencing of accession Bd21 [3], which contributed to several genetic and genomic resources including Phytozome [4] and Gramene [5] and gave rise to initiatives like BrachyPan (Brachypodium pan-genome) [6]. Consequently, Brachypodium became an object of intense research in many fields serving in understanding interaction of grasses with viruses [7], bacteria [8], fungi [9] and invertebrates [10] as well as their responses to abiotic stresses [11].…”
Section: Introductionmentioning
confidence: 99%
“…The wheat cultivar, named Wenmai 19 (Triticum aestivum) was proven to be susceptible to CCN, and H. avenae also infects and develops in Triticum urartu and Aegilops tauschii but not in Brachypodium distachyon (Kong et al 2016). The Hordeum vulgare cultivar Skiff showed susceptibility, while the cultivar Chebec was resistant (Aditya et al 2015).…”
Section: Introductionmentioning
confidence: 99%